STRATEGI PROMOSI DESTINASI WISATA DINAS PARIWISATA PROVINSI SUMATERA BARAT - Syahputra, Rahmadani Syahputra1,; Yuliana, Yuliana; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2017)
This research aims to determine the strategy for the promotion of tourist destinations Tourism Office of West Sumatra with bulk sales indicators, sales promotions and direct marketing are seen from the internal factors of the strengths and weaknesses as well as the external factors in the form of opportunities and threats. This research is descriptive research with qualitative data. Engineering data collection done by the method of interview, observation, and documentation involving the informant by using purposive sampling technique. The strategy of the promotion of tourist destinations can be: 1) cooperation with several companies such as civilian airlines to promote tourist destinations in the inflight magazine. 2) cooperating with the Office of tourism in other provinces to barter in conducting promotional activities tourist destinations. 3) maximize the use of the media promotion in open areas such as billboards or billboards. 4) follow more tourism promotion activities at the national and international levels.Keywords: Promotion Strategy, Tourist Destinations